Noncommunicable diseases among HIV-infected persons in low-income and middle-income countries: a systematic review and meta-analysis. (1st July 2018) - Patel, Pragna; Rose, Charles E.; Collins, Pamela Y.; Nuche-Berenguer, Bernardo; Sahasrabuddhe, Vikrant V.; Peprah, Emmanuel; Vorkoper, Susan; Pastakia, Sonak D.; Rausch, Dianne; Levitt, Naomi S.
Abstract : Objective: To appropriately identify and treat noncommunicable diseases (NCDs) among persons living with HIV (PLHIV) in low-and-middle-income countries (LMICs), it is imperative to understand the burden of NCDs among PLHIV in LMICs and the current management of the diseases. Design: Systematic review and meta-analysis. Methods: We examined peer-reviewed literature published between 1 January 2010 and 31 December 2016 to assess currently available evidence regarding HIV and four selected NCDs (cardiovascular disease, cervical cancer, depression, and diabetes) in LMICs with a focus on sub-Saharan Africa. The databases, PubMed/MEDLINE, Cochrane Review, and Scopus, were searched to identify relevant literature. For conditions with adequate data available, pooled estimates for prevalence were generated using random fixed effects models. Results: Six thousand one hundred and forty-three abstracts were reviewed, 377 had potentially relevant prevalence data and 141 were included in the summary; 57 were selected for quantitative analysis. Pooled estimates for NCD prevalence were hypertension 21.2% (95% CI 16.3–27.1), hypercholesterolemia 22.2% (95% CI 14.7–32.1), elevated low-density lipoprotein 23.2% (95% CI 15.2–33.6), hypertriglyceridemia 27.2% (95% CI 20.7–34.8), low high-density lipoprotein 52.3% (95% CI 35.6–62.8), obesity 7.8% (95% CI 4.3–13.9), and depression 24.4% (95% CI 12.5–42.1). Invasive cervical cancer and diabetes prevalence were 1.3–1.7 and 1.3–18%, respectively. Few NCD-HIV integrated programs with screening and management approaches that are contextually appropriate for resource-limited settings exist. Conclusion: Improved data collection and surveillance of NCDs among PLHIV in LMICs are necessary to inform integrated HIV/NCD care models. Although efforts to integrate care exist, further research is needed to optimize the efficacy of these programs. Abstract : Supplemental Digital Content is available in the text